Exploring the Neural Structures Underlying the Procedural Memory Network as Predictors of Language Ability in Children and Adolescents With Autism Spectrum Disorder and Attention Deficit Hyperactivity Disorder - Sanjeevan, Teenu; Hammill, Christopher; Brian, Jessica; Crosbie, Jennifer; Schachar, Russell; Kelley, Elizabeth; Liu, Xudong; Nicolson, Robert; Iaboni, Alana; Day Fragiadakis, Susan; Ristic, Leanne; Lerch, Jason P.; et al. (Frontiers in Human Neuroscience, 2020)
Introduction: There is significant overlap in the type of structural language impairments exhibited by children with Autism Spectrum Disorder (ASD) and children with Attention Deficit Hyperactivity Disorder (ADHD). This similarity suggests that the cognitive impairment(s) contributing to the structural language deficits in ASD and ADHD may be shared. Previous studies have speculated that procedural memory deficits may be the shared cognitive impairment. The Procedural Deficit Hypothesis (PDH) argues that language deficits can be explained by differences in the neural structures underlying the procedural memory network. This hypothesis is based on the premise that the neural structures comprising the procedural network support language learning. In this study, we aimed to test the PDH in children with ASD, ADHD and typical development (TD). Methods: One hundred and sixty-three participants (ages 10 – 21): 91 with ASD, 26 with ADHD and 46 with TD, completed standardized measures of cognitive and language ability as well as structural magnetic resonance imaging. We compared the structural language abilities, the neural structures underlying the procedural memory network and the relationship between structural language and neural structure across diagnostic groups. Results: Our analyses revealed that while the structural language abilities differed across ASD, ADHD and TD groups, the thickness, area and volume of the structures supporting the procedural memory network were not significantly different between groups. Also, several neural structures were associated with structural language abilities across diagnostic groups. Only two of these structures, the inferior frontal gyrus and the left superior parietal gyrus, are linked to the procedural memory network. Conclusions: The inferior frontal gyrus and the left superior parietal gyrus, have well-established roles in language learning independent of their role as part of the procedural memory system. Other structures such as the caudate and cerebellum, with critical roles in the procedural memory network, were not associated with structural language abilities across diagnostic groups. It is unclear whether the procedural memory network plays a fundamental role in language learning in ASD, ADHD and TD.